The Distribution of Ki-67 and Doublecortin-Immunopositive Cells in the Brains of Three Strepsirrhine Primates: Galago demidoff, Perodicticus potto, and Lemur catta. (21st February 2018) - Fasemore, Thandi M.; Patzke, Nina; Kaswera-Kyamakya, Consolate; Gilissen, Emmanuel; Manger, Paul R.; Ihunwo, Amadi O.
Graphical abstract: Highlights: The distribution of cells expressing Ki-67 and doublecortin was examined in prosimian primate brains. These cells indicate adult neurogenesis and were found in similar locations to that seen in other primates. A temporal migratory stream, supplying the piriform cortex, was observed in all species examined. Doublecortin-immunopositive cells were observed in the cerebellar cortex of all species examined. Abstract: This study investigated the pattern of adult neurogenesis throughout the brains of three prosimian primate species using immunohistochemical techniques for endogenous markers of this neural process. Two species, Galago demidoff and Perodicticus potto, were obtained from wild populations in the primary rainforest of central Africa, while one species, Lemur catta, was captive-bred. Two brains from each species, perfusion-fixed with 4% paraformaldehyde, were sectioned (50 µm section thickness) in sagittal and coronal planes. Using Ki-67 and doublecortin (DCX) antibodies, proliferating cells and immature neurons were identified in the two canonical neurogenic sites of mammals, the subventricular zone of the lateral ventricle (SVZ) giving rise to the rostral migratory stream (RMS), and the subgranular zone of the dentate gyrus of the hippocampus. In addition a temporal migratory stream (TMS), emerging from the temporal horn of the lateral ventricle to supply the piriform cortex and adjacent brain regions with new neurons, was also evident in the three prosimian species. While no Ki-67-immunoreactive cells were observed in the cerebellum, DCX-immunopositive cells were observed in the cerebellar cortex of all three species. These findings are discussed in a phylogenetic context.